2021
DOI: 10.21203/rs.3.rs-662637/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

De-implementing Low-Value Care in Cancer Care Delivery: A Systematic Review

Abstract: Background Accumulating evidence suggests that interventions to de-implement low-value services are urgently needed. While medical societies and educational campaigns such as Choosing Wisely have developed several guidelines and recommendations pertaining to low-value care, little is known about interventions that exist to de-implement low-value care in oncology settings. We conducted this review to summarize the literature on interventions to de-implement low-value care in oncology settings, define an agenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Studies investigating strategies to reduce LVC have been published in a broad range of journals, typically within specific clinical and medical care areas, from microbiological research on antimicrobial resistance to potentially inappropriate medication for the elderly [2]. Studies on strategies for de-implementation have also focused on specific LVC within fields such as nursing [25], low-value blood management techniques in primary hip and knee arthroplasty [26], pharmacological prescriptions [27], and cancer [28]. An exception is a systematic review of de-implementation strategies covering a wide range of clinical areas [29] that found promising results for clinical decision support and performance feedback, concluding that multicomponent strategies addressing both clinicians and patients had the greatest potential for reducing LVC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies investigating strategies to reduce LVC have been published in a broad range of journals, typically within specific clinical and medical care areas, from microbiological research on antimicrobial resistance to potentially inappropriate medication for the elderly [2]. Studies on strategies for de-implementation have also focused on specific LVC within fields such as nursing [25], low-value blood management techniques in primary hip and knee arthroplasty [26], pharmacological prescriptions [27], and cancer [28]. An exception is a systematic review of de-implementation strategies covering a wide range of clinical areas [29] that found promising results for clinical decision support and performance feedback, concluding that multicomponent strategies addressing both clinicians and patients had the greatest potential for reducing LVC.…”
Section: Introductionmentioning
confidence: 99%
“…An exception is a systematic review of de-implementation strategies covering a wide range of clinical areas [29] that found promising results for clinical decision support and performance feedback, concluding that multicomponent strategies addressing both clinicians and patients had the greatest potential for reducing LVC. Another review [28] focused specifically on cancer care similarly found that most de-implementation strategies were multifaceted. The most widely used strategies were audit and feedback, use of clinical champions, educating clinicians through developing and disseminating guidelines, and decisionsupport tools.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating strategies to reduce LVC have been published in a broad range of journals, typically within speci c clinical and medical care areas, from microbiological research on antimicrobial resistance to potentially inappropriate medication for the elderly (9). Studies on strategies for de-implementation have also focused on speci c LVC within elds such as nursing (26), low-value blood management techniques in primary hip and knee arthroplasty (27), pharmacological prescriptions (28), and cancer (29). An exception is a systematic review of de-implementation strategies covering a wide range of clinical areas (30) that found promising results for clinical decision support and performance feedback, concluding that multicomponent strategies addressing both clinicians and patients had the greatest potential for reducing LVC.…”
Section: Introductionmentioning
confidence: 99%
“…An exception is a systematic review of de-implementation strategies covering a wide range of clinical areas (30) that found promising results for clinical decision support and performance feedback, concluding that multicomponent strategies addressing both clinicians and patients had the greatest potential for reducing LVC. Another review (29) focused speci cally on cancer care similarly found that most de-implementation strategies were multifaceted. The most widely used strategies were audit and feedback, use of clinical champions, educating clinicians through developing and disseminating guidelines, and decision-support tools.…”
Section: Introductionmentioning
confidence: 99%